Islamic Religious Education Literacy and Numeration In the Perspective of the Al-Quran and Hadith - Sofa, Ainur Rofiq; Mukni’ah; Mashudi (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
The word Iqra 'is usually translated as